2010
DOI: 10.1007/s12020-010-9412-7
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 receptor gene polymorphism and the level of physical activity in men (HALS Study)

Abstract: Melanocortin plays an important role in the energy balance in humans. Actions of melanocortin are exerted through activation of five receptors among which the melanocortin-4 receptor (MC4R) is especially abundant within the central nervous system (CNS). It has been proved that genetic variations of the MC4R gene are associated with the energy intake. Recent data has suggested that MC4R gene polymorphism might influence physical activity/energy expenditure as well. Our aim was to search for associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In non-obese subjects, the incidence of the carriers varied from 0% (Germany), 1% to 3.3% (Italy), 2.8% (Finland), up to 9% (Turkey). Recently, the V103I polymorphism was also studied in a cohort of 311 Polish adults (mean BMI = 27) in relation to their physical activity (Jóźków et al 2011 ). The incidence of the 103I variant carriers was high (6.4%) and, in addition, one patient (0.3%) had a homozygous 103I/103I genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In non-obese subjects, the incidence of the carriers varied from 0% (Germany), 1% to 3.3% (Italy), 2.8% (Finland), up to 9% (Turkey). Recently, the V103I polymorphism was also studied in a cohort of 311 Polish adults (mean BMI = 27) in relation to their physical activity (Jóźków et al 2011 ). The incidence of the 103I variant carriers was high (6.4%) and, in addition, one patient (0.3%) had a homozygous 103I/103I genotype.…”
Section: Discussionmentioning
confidence: 99%
“…More than 40% of the volunteers held a university degree and we found that longer education was associated with fewer symptoms. We underlined a higher than average level of physical activity of the enrolled men in our previous publication [18]. The major strength of this study is that the investigated men derived from a genetically homogeneous region, they were generally healthy and did not receive drugs that could interfere with the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the genotyping of 5-HT, MC and DA receptors have been described in our previous reports [16,17,18]. …”
Section: Methodsmentioning
confidence: 99%
“…Other obesity-related genes similarly interact with physical inactivity to predict lower BMI, including ACE (Moran et al, 2005), ADRB2 (Corbalán et al, 2002; Lagou et al, 2012; Meirhaeghe et al, 1999), ADRB3 (Marti del Moral et al, 2002), PPARGC1A (Ridderstråle et al, 2006), SEC16B (Ahmad et al, 2013), and UPC3 (Otabe et al, 2000). Although several other studies have failed to observe such interactive effects (Berentzen et al, 2005; Cauchi et al, 2009; Edwards et al, 2013; Jonsson et al, 2009; Jóźków et al, 2011; Kaakinen et al, 2010; Lappaläinen et al, 2009; Liem et al, 2010; Liu et al, 2010; Nakashima et al, 2013; Tan et al, 2008) or have found interaction effects in the opposite direction (Alonso et al, 2005), several experimental studies of interventions for weight loss that compare wild type individuals and persons with a risk allele have provided compelling evidence for physical activity as a moderator of genetic influences on high adiposity or obesity (de Luis et al, 2006; Shiwaku et al, 2003; but see Müller et al, 2008). …”
Section: Behavioral and Environmental Influences On Genetic Variationmentioning
confidence: 94%